A ceramic component with complex structure made of multiple materials and printing method thereof
Through multi-tip printing and phased heating treatment, the partition design of high content and cross-linked network ceramic ink is solved, and the problem of the existing technology being unable to print out the structurally complete multi-material complex structure ceramic parts is realized. Improved density and stability, suitable for applications in the fields of aerospace and electronic information.
Patent Information
- Application Number
- CN202411252602.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-09
AI Technical Summary
The prior art cannot effectively print out structurally complete multi-material complex structural ceramic parts, especially under the harsh service conditions in the fields of aerospace and electronic information, and it is difficult to manufacture complex-shaped ceramic parts.
Using multi-tip printing method, high-content ceramic ink and ceramic ink with cross-linking network are used respectively. Through phased heating and shaping processing, the material partition design of the three-dimensional structure is optimized, and the cross-linking network ink is used to reduce deformation and high-filling ink increases density. , form complex structural ceramic parts that have both density and structural stability.
It has achieved the printing of complex structural ceramic parts with complete structure, high density and stability, solving the problems of density and structural integrity of ceramic parts, and is suitable for large-scale production.
Smart Images

Figure CN118769351B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of additive manufacturing technology, and in particular to a multi-material complex structure ceramic part and a printing method thereof. Background Art
[0002] Ceramic materials have the characteristics of high strength, wear resistance, corrosion resistance and high temperature resistance, and have good application prospects in aerospace, biomedicine, electronic information and other fields. High-performance and functional ceramics have the advantages of high mechanical strength, high resistivity, good electrical insulation, good chemical stability, good biocompatibility and low cost, and have important applications in aerospace, machinery, chemical industry, electronics, biomedicine and many other fields.
[0003] However, with the continuous development of aerospace and electronic information technology, increasingly harsh service conditions and more complex equipment designs have put forward higher requirements on materials and structures. How to manufacture complex-shaped ceramic parts used in the above fields has become an important issue. Summary of the invention
[0004] The present application provides a ceramic component with a complex structure of multiple materials and a printing method thereof, which at least solves the technical problem that the prior art cannot print ceramic components with a complex structure of multiple materials with complete structures.
[0005] In order to solve the above technical problems, the embodiment of the present application provides: a printing method for a ceramic part with a complex structure of multiple materials, comprising the following steps:
[0006] The printing method uses multiple nozzles, and the nozzles are respectively loaded with high-content ceramic ink and ceramic ink with a cross-linked network;
[0007] During the printing process, the main bearing structure is printed with ceramic ink with a cross-linked network, and the filling structure is printed with high-content ceramic ink;
[0008] After the printing is completed, a printed product is obtained; the printed product is subjected to a stage-by-stage heating and shaping treatment to obtain a ceramic product with a complex structure of multiple materials.
[0009] As some optional embodiments of the present application, the printing process parameters of the high-content ceramic ink and the ceramic ink with a cross-linked network are: needle diameter 0.5~1.0 mm, pressure 0.25~1 MPa, and printing speed 5~20 mm / s.
[0010] As some optional embodiments of the present application, the process parameters of the staged heating and shaping treatment are:
[0011] Room temperature to 80~200℃, heating rate 1~4℃ / min, keep warm for 1~2 h;
[0012] Then heat up to 600℃, heating rate 1~4℃ / min, keep warm for 1~2 h;
[0013] Then increase the temperature to 1300~1600℃ at a rate of 1~4℃ / min and keep it at this temperature for 2~5h.
[0014] As some optional embodiments of the present application, the high-content ceramic ink includes the following components in parts by weight:
[0015] 30~60 parts of ceramic micron powder,
[0016] 10~20 parts of ceramic nanopowder,
[0017] 1~5 parts of water retaining agent,
[0018] Sintering aid 5~10 parts,
[0019] Dispersant 0.1~1 part,
[0020] 10~50 parts of deionized water,
[0021] A total of 100 copies;
[0022] The high-content ceramic ink has a shear rate of 1 to 100 s at room temperature. -1 When the viscosity is 10~100 mPa•s.
[0023] As some optional embodiments of the present application, the water-retaining agent includes at least one of polyvinyl alcohol, methyl cellulose and sodium acrylate.
[0024] As some optional embodiments of the present application, the dispersant includes at least one of sodium silicate, sodium carbonate, polyethylene glycol, sodium citrate, ammonium citrate, sodium tannate, sodium gallate and sodium oxalate.
[0025] As some optional embodiments of the present application, the sintering aid includes at least one of magnesium oxide, silicon dioxide and titanium dioxide.
[0026] As some optional embodiments of the present application, the ceramic ink having a cross-linked network comprises the following components in parts by weight:
[0027] 30~60 parts of ceramic micron powder,
[0028] 10~20 parts of ceramic nanopowder,
[0029] Cross-linked network polymer 5~20 parts,
[0030] Sintering aid 1~5 parts,
[0031] A total of 100 copies;
[0032] The ceramic ink with a cross-linked network is subjected to a shear rate of 1 to 100 s at room temperature. -1 When the viscosity is 10~100mPa•s.
[0033] As some optional embodiments of the present application, the cross-linked network polymer is selected to include at least one of epoxy resin, silicone rubber and acrylate cross-linked polymer.
[0034] As some optional embodiments of the present application, the ceramic selection includes at least one of alumina ceramics, silicon carbide ceramics and silicon nitride ceramics.
[0035] As some optional embodiments of the present application, the sintering aid includes at least one of magnesium oxide, silicon dioxide and titanium dioxide.
[0036] As some optional embodiments of the present application, the high-content ceramic ink is prepared by the following steps:
[0037] Under normal temperature conditions, add a water retaining agent, a dispersant, and a sintering aid into deionized water and mix them thoroughly to prepare a mixed liquid for standby use;
[0038] Ceramic micron powder and ceramic nano powder are added into the mixed liquid and mixed thoroughly to obtain high-content ceramic ink.
[0039] As some optional embodiments of the present application, the ceramic ink having a cross-linked network is prepared by the following steps:
[0040] Under normal temperature conditions, the cross-linked network polymer and the sintering aid are fully mixed and used as a mixed liquid for standby use;
[0041] After adding ceramic micron powder, ceramic nano powder and a cross-linking agent into the mixed liquid and mixing them thoroughly, a ceramic ink with a cross-linking network is obtained.
[0042] On the other hand, an embodiment of the present application provides a ceramic component with a complex structure of multiple materials, which is prepared by the method described above.
[0043] Compared with the prior art, the present application provides a method for printing a ceramic component with a multi-material complex structure, comprising the following steps: adopting a multi-nozzle printing method, wherein the nozzles are respectively loaded with high-content ceramic ink and ceramic ink with a cross-linked network; during the printing process, the main bearing structure is printed with ceramic ink with a cross-linked network, and the filling structure is printed with high-content ceramic ink; after the printing is completed, a printed component is obtained; the printed component is subjected to a staged heating and shaping treatment to obtain a ceramic component with a multi-material complex structure. It can be seen that the present application optimizes the three-dimensional structure of the component through a reasonable structural design, adopts partitioned materials to manufacture different areas of the three-dimensional structure, adopts cross-linked network ink to reduce the deformation of the component in the easily deformed area of the three-dimensional structure, and adopts high-filling ink to increase the density of the component in the remaining areas, thereby printing a ceramic component with a complex structure that has both density and structural stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In order to more clearly illustrate the specific implementation of the present application or the technical solution in the prior art, the following is a brief introduction to the drawings required for the specific implementation or the prior art description. In all drawings, similar elements or parts are generally identified by similar reference numerals. In the drawings, each element or part is not necessarily drawn according to the actual scale.
[0045] Figure 1 A three-dimensional design drawing of the printed product of Example 1 of the present application;
[0046] Figure 2 This is a microscopic mechanism diagram of the cross-linked network polymer of Example 1 of the present application;
[0047] Figure 3 A three-dimensional design drawing of the printed product of Example 2 of the present application;
[0048] Figure 4 This is a three-dimensional design drawing of the printed product of Example 3 of the present application.
[0049] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0050] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0051] As an emerging three-dimensional molding technology, additive manufacturing technology has the advantages of digital manufacturing, dimensionality reduction manufacturing, and rapid prototyping manufacturing. It has great research prospects and industrial value and has received widespread attention in various fields. The main additive manufacturing technical methods include fused deposition modeling (FDM), selective laser sintering (SLS), photo-stereolithography (SLA), and ink direct writing (DIW). Compared with other technologies, DIW technology is based on room temperature processing, has fewer stringent requirements on materials, and is expected to prepare ceramic slurry parts with high filling. For example, some technologies disclose a moldless direct writing preparation method for ceramic-based three-dimensional structures and a ceramic-based photosensitive slurry, which uses photo-curing assisted molding. Since the slurry needs to have a certain fluidity and ductility during the photo-curing process, it is difficult to prepare ceramic products with high solid content.
[0052] At present, most of the research on ink direct writing ceramic parts is limited to the three-dimensional molding of materials, such as ignoring the problems of the integrity and density of the printed parts after sintering. For example, there is a technology that mixes ceramic precursor materials, ceramic particles, adhesives and organic solvents to prepare ceramic precursor printing slurry, and prepares a ceramic precursor model with a 3D regular pore structure through ink direct writing 3D printing. It mainly optimizes the formula and ignores the problem of pore collapse during the sintering process and whether the structural integrity can be maintained.
[0053] The multi-material additive manufacturing technology proposed in this application can integrate multiple materials into one-piece molding, and realize the collaborative manufacturing of materials with different performances and functions on the basis of manufacturing complex structures. Based on the optimized structure, bionic laminated structures and gradient composite materials can be obtained. It is expected to solve the problems of density and structural integrity of ceramic parts manufactured by additive manufacturing. That is, this application introduces multi-material additive manufacturing technology, which can integrate multiple materials into one-piece molding, and realize the collaborative manufacturing of materials with different performances and functions on the basis of manufacturing complex structures. Based on the optimized structure, bionic laminated structures and gradient composite materials can be obtained. Through the design of different materials and the compounding of structures, the problems of density and structural integrity of ceramic parts manufactured by additive manufacturing are solved.
[0054] Specifically, the present application provides a method for preparing ceramic parts with excellent structural integrity by multi-material printing, which is optimized from two aspects: material and structural design. The use of mesoporous structures such as honeycomb structures inside additively manufactured parts can reduce deformation of parts caused by thermal stress. Cross-linked network structure polymers can improve the structural integrity of parts, and the wrapping effect of cross-linked network polymers on ceramics can improve the casting strength of parts, thereby taking into account the density and structural integrity of parts.
[0055] In some specific embodiments, the multi-material complex structure ceramic parts are obtained by printing through the following steps: a multi-nozzle printing method is adopted, and the nozzles are respectively loaded with high-content ceramic ink and ceramic ink with a cross-linked network; during the printing process, the main bearing structure is printed with ceramic ink with a cross-linked network, and the filling structure is printed with high-content ceramic ink; after the printing is completed, a printed part is obtained; the printed part is subjected to staged heating and shaping treatment to obtain a multi-material complex structure ceramic part.
[0056] Among them, the printing process parameters of the high-content ceramic ink and the ceramic ink with a cross-linked network are: needle diameter 0.5~1.0 mm, pressure 0.25~1 MPa, and printing speed 5~20 mm / s.
[0057] Among them, the process parameters of the staged heating and shaping treatment are: room temperature to 80~200℃, heating rate 1~4℃ / min, keeping warm for 1~2 hours; then heating to 600℃, heating rate 1~4℃ / min, keeping warm for 1~2 hours; then heating to 1300~1600℃ at a rate of 1~4℃ / min, keeping warm for 2~5 hours.
[0058] The high-content ceramic ink comprises the following components by weight: 30-60 parts of ceramic micron powder, 10-20 parts of ceramic nano powder, 1-5 parts of water retaining agent, 5-10 parts of sintering aid, 0.1-1 parts of dispersant, and 10-50 parts of deionized water, totaling 100 parts; the high-content ceramic ink has a shear rate of 1-100 s at room temperature. -1 When the viscosity is 10~100 mPa•s.
[0059] It should be noted that the water-retaining agent includes at least one of polyvinyl alcohol, methyl cellulose and sodium acrylate; the dispersant includes at least one of sodium silicate, sodium carbonate, polyethylene glycol, sodium citrate, ammonium citrate, sodium tannate, sodium gallate and sodium oxalate; and the sintering aid includes at least one of magnesium oxide, silicon dioxide and titanium dioxide.
[0060] The high-content ceramic ink is prepared by the following steps: at room temperature, a water retaining agent, a dispersant, and a sintering aid are added to deionized water and fully mixed to prepare a mixed liquid for use; ceramic micron powder and ceramic nano powder are added to the mixed liquid and fully mixed to obtain a high-content ceramic ink.
[0061] The ceramic ink with a cross-linked network comprises the following components by weight: 30 to 60 parts of ceramic micron powder, 10 to 20 parts of ceramic nanopowder, 5 to 20 parts of cross-linked network polymer, and 1 to 5 parts of sintering aid, totaling 100 parts; the ceramic ink with a cross-linked network has a shear rate of 1 to 100 s at room temperature.-1 When the viscosity is 10~100 mPa•s.
[0062] It should be noted that the cross-linked network polymer is selected to include at least one of epoxy resin, silicone rubber and acrylate cross-linked polymer. Generally, the cross-linked network polymer is usually composed of two components: a polymer prepolymer and a cross-linking agent; the ceramic is selected to include at least one of alumina ceramic, silicon carbide ceramic and silicon nitride ceramic; the sintering aid includes at least one of magnesium oxide, silicon dioxide and titanium dioxide.
[0063] The ceramic ink with a cross-linked network is prepared by the following steps: at room temperature, a cross-linked network polymer prepolymer and a sintering aid are fully mixed and used as a mixed liquid for standby use; ceramic micron powder, ceramic nano powder and a cross-linking agent are added to the mixed liquid and fully mixed to obtain a ceramic ink with a cross-linked network. Generally, the mixing mass ratio of the prepolymer and the cross-linking agent in the cross-linked network polymer is usually 10:1.
[0064] Generally, the ceramic can be any type and model of ceramic sold on the market, or a ceramic raw material prepared according to the prior art; the purpose of adding the dispersant is to enable the ceramic filler to be evenly dispersed. Of course, the present application may also add other processing aids such as antioxidants, flame retardants, anti-aging agents known in the prior art, and may also add other functional fillers such as carbon-based fillers, conductive fillers, etc. according to actual technical purposes or processing conditions and other factors. Those skilled in the art may refer to the prior art to determine the amount of the above-mentioned other functional fillers to be added. However, the premise is that these processing aids and fillers shall not have an adverse effect on the realization of the purpose of this application and the achievement of the excellent effects of this application.
[0065] It should be noted that the viscosity defined in the technical solution of this application is obtained through a lot of exploration and experimental summary to meet the printability of the ceramic ink system. Those skilled in the art should know that in order to meet the requirements of direct ink printing and ink materials with printability, the required viscosity coefficient standard should be changed according to the specific ink materials used, and viscosity is not the only criterion for measuring whether the ink material is printable.
[0066] Compared with the prior art, this application has the following beneficial effects:
[0067] This application uses multi-material additive manufacturing technology to prepare complex structure ceramic parts with multiple materials in one by a simple one-step molding method based on the design of materials and structures. This application optimizes the three-dimensional structure of the part through reasonable structural design, uses partitioned materials to manufacture different areas of the three-dimensional structure, uses cross-linked network ink in the variable area of the three-dimensional structure to reduce the deformation of the part, and uses high-filling ink in the remaining areas to increase the density of the part. The product prepared by this application is a complex structure ceramic part with both density and structural stability. The preparation method of this application has mature process conditions, a simple preparation process, low manufacturing costs, and is suitable for large-scale production.
[0068] It can be seen that the present application adopts multi-material additive manufacturing technology to prepare ceramic parts with complex structures, and solves the problems of poor density and weak structural stability of ceramic parts. First, ceramic inks of different properties are prepared: high-content ceramic inks and ceramic inks with cross-linked networks. Different inks are printed in different areas of the parts, and the deformable areas of the parts are made of ceramic inks with cross-linked networks to improve the structural stability of the parts; the remaining areas of the parts are made of high-content ceramic inks to improve the density of the parts. In addition, the use of hollow structures such as honeycomb structures inside the additively manufactured parts can reduce the deformation of the parts caused by thermal stress. When the final part is heat treated, at low temperature, the wrapping effect of the cross-linked network molecules on the ceramic can improve the casting strength. At high temperature, by adding sintering aids, the ceramics and the aids form a stable crystalline phase, accompanied by volume expansion to offset the volume shrinkage of the cross-linked network pyrolysis, thereby obtaining a complex structure ceramic part that takes into account both density and structural integrity.
[0069] Below, in conjunction with specific embodiments, the technical solution described in the present application is described in detail so that those skilled in the art can understand the technical solution of the present application:
[0070] Example 1
[0071] The high-content ceramic ink used for printing to increase the density of the workpiece, the raw materials of which mainly include the following components by weight:
[0072] 50 parts of ceramic micron powder,
[0073] 30 parts of ceramic nanopowder,
[0074] 0.5 parts of water retaining agent,
[0075] 4 parts of sintering aid,
[0076] 0.5 parts of dispersant,
[0077] 15 parts of deionized water;
[0078] A total of 100 copies.
[0079] Wherein, the ceramic powder is selected as alumina powder, the water retaining agent is selected as sodium carboxymethyl cellulose, the sintering aid is selected as magnesium oxide, and the dispersant is selected as polyethylene glycol;
[0080] The method for preparing the high-content ceramic ink for printing and increasing the density of the workpiece comprises the following steps:
[0081] (1) At room temperature, add sodium carboxymethyl cellulose, polyethylene glycol, and magnesium oxide to deionized water and mix thoroughly to prepare a mixed liquid for later use;
[0082] (2) adding ceramic fillers to the mixed solution obtained in step (1) in three steps and mixing them thoroughly to prepare a mixed slurry for later use;
[0083] (3) After being fully mixed, the high-content ceramic ink is subjected to a shear rate of 1 to 100 s at room temperature. -1 When the viscosity is 80mPa•s.
[0084] The ceramic ink with a cross-linked network used for printing to improve the structural integrity of a workpiece mainly comprises the following components by weight:
[0085] 45 parts of ceramic micron powder,
[0086] 20 parts of ceramic nanopowder,
[0087] 30 parts of cross-linked network polymer,
[0088] 5 parts of sintering aid,
[0089] A total of 100 copies.
[0090] Wherein, the ceramic powder is selected as alumina powder, the cross-linked network polymer is selected as polydimethylsiloxane, and the sintering aid is selected as magnesium oxide.
[0091] The method for preparing the above-mentioned ceramic ink having a cross-linked network for printing to improve the structural integrity of a workpiece comprises the following steps:
[0092] (1) Under normal temperature conditions, fully mix the polydimethylsiloxane prepolymer and magnesium oxide to prepare a mixed liquid for standby use;
[0093] (2) adding alumina filler and cross-linking agent to the mixed solution obtained in step (1) and mixing them thoroughly to prepare a mixed slurry for later use;
[0094] (3) After being fully mixed, the viscosity of the high-content ceramic ink is 60 mPa•s at a shear rate of 100 s-1 at room temperature.
[0095] A method for printing alumina ceramic parts with excellent structural integrity by multi-material printing comprises the following steps:
[0096] (1) Using a multi-nozzle printing method, respectively loading high-content alumina ceramic ink and alumina ceramic ink with a cross-linked network;
[0097] (2) The main bearing structure during the printing process is a ceramic ink with a cross-linked network, and the filling structure is a high-content ceramic ink. The three-dimensional design diagram of the alumina ceramic part is as follows: Figure 1 As shown in the figure, the idea of reinforced cement hybrid structure in architectural design is adopted, and a multi-material integrated component with good support is constructed using cross-linked network ink and high-content ceramic ink; wherein the microscopic mechanism diagram of the cross-linked network ink and high-content ceramic ink is as shown in the figure. Figure 2 As shown;
[0098] (3) The process parameters of the above ink direct writing printing are: needle diameter 0.6 mm, pressure 1 MPa, printing speed 8 mm / s;
[0099] (4) After printing, the temperature is raised in stages, from room temperature to 100 °C, at a rate of 4 °C / min, and kept at this temperature for 2 h. The temperature is then raised to 600 °C, at a rate of 1 °C / min, and kept at this temperature for 1 h. The temperature is then raised to 1550 °C at a rate of 4 °C / min, and kept at this temperature for 5 h.
[0100] Example 2
[0101] This embodiment adopts multi-material additive manufacturing technology to prepare an alumina ceramic component that has both compactness and structural stability.
[0102] The high-content ceramic ink used for printing to increase the density of the workpiece, the raw materials of which mainly include the following components by weight:
[0103] 50 parts of ceramic micron powder,
[0104] 30 parts of ceramic nanopowder,
[0105] 0.5 parts of water retaining agent,
[0106] 4 parts of sintering aid,
[0107] 0.5 parts of dispersant,
[0108] 15 parts of deionized water;
[0109] A total of 100 copies.
[0110] Wherein, the ceramic powder is selected as alumina powder,
[0111] The water retaining agent is sodium carboxymethyl cellulose.
[0112] The sintering aid is selected as magnesium oxide;
[0113] The dispersant is selected as polyethylene glycol;
[0114] The method for preparing the high-content ceramic ink for printing and increasing the density of the workpiece comprises the following steps:
[0115] (1) At room temperature, add sodium carboxymethyl cellulose, polyethylene glycol, and magnesium oxide to deionized water and mix thoroughly to prepare a mixed liquid for later use;
[0116] (2) adding ceramic fillers to the mixed solution obtained in step (1) in three steps and mixing them thoroughly to prepare a mixed slurry for later use;
[0117] (3) After being fully mixed, the high-content ceramic ink is subjected to a shear rate of 1 to 100 s at room temperature. -1 When the viscosity is 80mPa•s.
[0118] The ceramic ink with a cross-linked network used for printing to improve the structural integrity of a workpiece mainly comprises the following components by weight:
[0119] 45 parts of ceramic micron powder,
[0120] 20 parts of ceramic nanopowder,
[0121] 30 parts of cross-linked network polymer,
[0122] 5 parts of sintering aid,
[0123] A total of 100 copies.
[0124] Wherein, the ceramic powder is selected as alumina powder,
[0125] The cross-linked network polymer is selected as polydimethylsiloxane,
[0126] The sintering aid is selected as magnesium oxide;
[0127] The method for preparing the above-mentioned ceramic ink having a cross-linked network for printing to improve the structural integrity of a workpiece comprises the following steps:
[0128] (1) Under normal temperature conditions, fully mix the polydimethylsiloxane prepolymer and magnesium oxide to prepare a mixed liquid for standby use;
[0129] (2) adding alumina filler and cross-linking agent to the mixed solution obtained in step (1) and mixing them thoroughly to prepare a mixed slurry for later use;
[0130] (3) After being fully mixed, the high-content ceramic ink is heated at room temperature at a shear rate of 100 s -1When the viscosity is 60mPa•s.
[0131] A method for printing alumina ceramic parts with excellent structural integrity by multi-material printing comprises the following steps:
[0132] (1) Using a multi-nozzle printing method, respectively loading high-content alumina ceramic ink and alumina ceramic ink with a cross-linked network;
[0133] (2) The main bearing structure during the printing process is a ceramic ink with a cross-linked network, and the filling structure is a high-content ceramic ink. The multi-material printing method is used to form an integrated structural component such as Figure 3 As shown;
[0134] (3) The process parameters of the above ink direct writing printing are: needle diameter 0.6 mm, pressure 1 MPa, printing speed 8 mm / s;
[0135] (4) After printing, the temperature is raised in stages, from room temperature to 100 °C, at a rate of 4 °C / min, and kept at this temperature for 2 h. The temperature is then raised to 600 °C, at a rate of 1 °C / min, and kept at this temperature for 1 h. The temperature is then raised to 1550 °C at a rate of 4 °C / min, and kept at this temperature for 5 h.
[0136] Example 3
[0137] This embodiment adopts multi-material additive manufacturing technology to prepare a silicon carbide ceramic component that has both compactness and structural stability.
[0138] The high-content ceramic ink used for printing to increase the density of the workpiece, the raw materials of which mainly include the following components by weight:
[0139] 55 parts of ceramic micron powder,
[0140] 30 parts of ceramic nanopowder,
[0141] 0.5 parts of water retaining agent,
[0142] 4 parts of sintering aid,
[0143] 0.5 parts of dispersant,
[0144] 10 parts of deionized water;
[0145] A total of 100 copies.
[0146] Wherein, the ceramic powder is selected as silicon carbide powder,
[0147] The water retaining agent is sodium carboxymethyl cellulose.
[0148] The sintering aid is selected as nano titanium dioxide;
[0149] The dispersant is selected as polyethylene glycol;
[0150] The method for preparing the high-content ceramic ink for printing and increasing the density of the workpiece comprises the following steps:
[0151] (1) At room temperature, add sodium carboxymethyl cellulose, polyethylene glycol, and titanium dioxide to deionized water and mix thoroughly to prepare a mixed liquid for later use;
[0152] (2) adding ceramic fillers to the mixed solution obtained in step (1) in three steps and mixing them thoroughly to prepare a mixed slurry for later use;
[0153] (3) After being fully mixed, the high-content ceramic ink is subjected to a shear rate of 1 to 100 s at room temperature. -1 When the viscosity is 90mPa•s.
[0154] The ceramic ink with a cross-linked network used for printing to improve the structural integrity of a workpiece mainly comprises the following components by weight:
[0155] 45 parts of ceramic micron powder,
[0156] 25 parts of ceramic nanopowder,
[0157] 25 parts of cross-linked network polymer,
[0158] 5 parts of sintering aid,
[0159] A total of 100 copies.
[0160] Wherein, the ceramic powder is selected as silicon carbide powder,
[0161] The cross-linked network polymer is selected as polydimethylsiloxane,
[0162] The sintering aid is selected as titanium dioxide;
[0163] The method for preparing the above-mentioned ceramic ink having a cross-linked network for printing to improve the structural integrity of a workpiece comprises the following steps:
[0164] (1) Under normal temperature conditions, fully mix the polydimethylsiloxane prepolymer and titanium dioxide to prepare a mixed liquid for later use;
[0165] (2) adding silicon carbide filler and cross-linking agent to the mixed solution obtained in step (1) and mixing them thoroughly to prepare a mixed slurry for later use;
[0166] (3) After being fully mixed, the high-content ceramic ink is heated at room temperature at a shear rate of 100 s -1 When the viscosity is 70mPa•s.
[0167] A method for printing a multi-material silicon carbide ceramic part with excellent structural integrity comprises the following steps:
[0168] (2) A multi-nozzle printing method is used to load high-content silicon carbide ceramic ink and silicon carbide ceramic ink with a cross-linked network respectively.
[0169] (3) The main bearing structure during the printing process is a ceramic ink with a cross-linked network, and the filling structure is a high-content ceramic ink, such as Figure 4 shown.
[0170] (4) The process parameters of the above ink direct writing printing are: needle diameter 0.6 mm, pressure 1.2 MPa, and printing speed 10 mm / s.
[0171] (5) After printing, the temperature is raised in stages, from room temperature to 100 °C, at a rate of 4 °C / min, and kept at this temperature for 2 h. The temperature is then raised to 600 °C, at a rate of 1 °C / min, and kept at this temperature for 2 h. The temperature is then raised to 1450 °C at a rate of 4 °C / min, and kept at this temperature for 5 h.
[0172] Experimental Example 1
[0173] AO-2 alumina powder was used to prepare cast alumina parts and single alumina printed parts. The multi-material alumina printed parts were the products of Example 1.
[0174] Test method: A universal mechanical testing machine is used to test standard size test specimens using the test methods specified in GB / T 8489-2006 (fine ceramic compression strength test) and GB / T 6569-2006 (fine ceramic bending strength test).
[0175] The test results are shown in Table 1:
[0176] Table 1
[0177]
[0178] It can be seen that the multi-material alumina parts prepared by the above method provided in this application have significantly improved mechanical properties compared to parts printed with single alumina ink, and have significantly improved volume shrinkage compared to cast alumina parts, and have great application potential.
[0179] The above are only preferred embodiments of the present application, and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. A printing method for multi-material complex structure ceramic parts, characterized in that: The following steps are involved: A multi-nozzle printing method is adopted, and the nozzles are respectively loaded with high-content ceramic ink and ceramic ink with a cross-linked network; the high-content ceramic ink comprises the following components by weight: 30-60 parts of ceramic micron powder, 10-20 parts of ceramic nanopowder, 1-5 parts of water retaining agent, 5-10 parts of sintering aid, 0.1-1 parts of dispersant, 10-50 parts of deionized water, a total of 100 parts; the high-content ceramic ink has a shear rate of 1-100 s at room temperature. -1 The viscosity is 10-100 mPa•s; the water retaining agent includes at least one of polyvinyl alcohol, methyl cellulose and sodium acrylate; the dispersant includes at least one of sodium silicate, sodium carbonate, polyethylene glycol, sodium citrate, ammonium citrate, sodium tannate, sodium gallate and sodium oxalate; the sintering aid includes at least one of magnesium oxide, silicon dioxide and titanium dioxide; the ceramic ink with a cross-linked network includes the following components in parts by weight: 30-60 parts of ceramic micron powder, 10-20 parts of ceramic nanopowder, 5-20 parts of cross-linked network polymer, 1-5 parts of sintering aid, a total of 100 parts; the ceramic ink with a cross-linked network has a shear rate of 1-100 s at room temperature. -1 When the viscosity is 10-100 mPa•s; the cross-linked network polymer comprises at least one of epoxy resin, silicone rubber and acrylate cross-linked polymer; During the printing process, the main bearing structure is printed with ceramic ink with a cross-linked network, and the filling structure is printed with high-content ceramic ink; After printing is completed, the printed product is obtained; The printed product is subjected to a stage-by-stage heating and shaping process to obtain a ceramic product with a complex structure of multiple materials.
2. The printing method of multi-material complex structure ceramic parts according to claim 1, characterized in that: The printing process parameters of the high-content ceramic ink and the ceramic ink with a cross-linked network are: needle diameter 0.5-1.0 mm, pressure 0.25-1 MPa, and printing speed 5-20 mm / s.
3. The printing method of multi-material complex structure ceramic parts according to claim 1, characterized in that: The process parameters of the staged heating and shaping treatment are: Room temperature to 80~200℃, heating rate 1~4℃ / min, keep warm for 1~2 h; Then heat up to 600℃, heating rate 1~4℃ / min, keep warm for 1~2 h; Then increase the temperature to 1300~1600℃ at a rate of 1~4℃ / min and keep it at this temperature for 2~5h.
4. The printing method of multi-material complex structure ceramic parts according to claim 1, characterized in that: The ceramic selection includes at least one of aluminum oxide ceramics, silicon carbide ceramics, and silicon nitride ceramics.
5. The printing method of multi-material complex structure ceramic parts according to claim 1, characterized in that: The sintering aid includes at least one of magnesium oxide, silicon dioxide and titanium dioxide.
6. The printing method of multi-material complex structure ceramic parts according to claim 1, characterized in that: The high-content ceramic ink is prepared by the following steps: Under normal temperature conditions, add a water retaining agent, a dispersant, and a sintering aid into deionized water and mix them thoroughly to prepare a mixed liquid for standby use; Ceramic micron powder and ceramic nano powder are added into the mixed liquid and mixed thoroughly to obtain high-content ceramic ink.
7. The printing method of multi-material complex structure ceramic parts according to claim 1, characterized in that: The ceramic ink having a cross-linked network is prepared by the following steps: Under normal temperature conditions, the cross-linked network polymer and the sintering aid are fully mixed and used as a mixed liquid for standby use; After adding ceramic micron powder, ceramic nano powder and a cross-linking agent into the mixed liquid and mixing them thoroughly, a ceramic ink with a cross-linking network is obtained.
8. A ceramic component with a complex structure of multiple materials, characterized in that: The method is prepared by the method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Layered ceramic based on fused deposition modeling and preparation method thereof
CN118146002A
KR1018504140000B1